Participation and performance by women and men in ski-mountaineering sprint races during the past decade - Fornasiero, A.; Callovini, A.; Fornoni, S.; Savoldelli, A.; Schena, F.; Holmberg, H.-C.; Bortolan, L. (The Journal of Sports Medicine and Physical Fitness, 2023)
BACKGROUND: The sprint is one of the two ski-mountaineering disciplines that will be held at the coming Milano Cortina 2026 Winter Olympics (Italy). To date little information exists on this novel Olympic discipline. METHODS: We characterized retrospectively the participation and performance in international male and female ski mountaineering sprint races from November 2012 to April 2022. Potential associations between sex and season with participation, as well as between sex, period, round and final ranking with parameters of performance were examined with linear-mixed models. RESULTS: The minimal performance time required for success (i.e., being eligible for the next round/winning a medal) decreased progressively from the qualifications (Qs) to the final (F). Finalists adopted a conservative strategy in the Qs, improving their performance in the quarter-finals (QFs) and semifinals (SFs). The best and second-best male skier and the best female skier improved their performances even further in the F, which appears to be a key feature for success. For women, the number of participants and level of competition increased over the decade, whereas male participation did not. During the last two seasons, male sprint winners performed relatively more slowly in the preliminary rounds leaving more room for improvement in the F, which could reflect increased specialization in this discipline. CONCLUSIONS: Our findings provide novel insights into ski-mountaineering sprint races that can guide competition strategies and could be of considerable importance in connection with the Milano Cortina 2026 Winter Olympics (Italy).